Formation rules of single phase solid solution in high entropy alloys. Issue 6 (12th April 2016) - Jiang, L.; Lu, Y.P.; Jiang, H.; Wang, T.M.; Wei, B.N.; Cao, Z.Q.; Li, T.J.
Abstract : A new empirical rule to form single phase solid solution structured high entropy alloys was proposed by integrating three dependent parameters, i.e. atomic size difference δ, mixing enthalpy Δ H mix and valence electron concentration VEC . It was found that the single phase face centred cubic solid solution will form if δ < 4.27%, − 7.27 kJ mol − 1  < Δ H mix  < 4 kJ mol − 1 and VEC >8, while the single phase body centred cubic solid solution will form in the case of δ < 4.27%, − 7.27 kJ mol − 1  < Δ H mix  < 4 kJ mol − 1 and VEC  < 6.87. This empirical rule was verified by typical high entropy alloys that have been reported.